Limit-point type solutions of nonlinear differential equations - Mustafa, OG; Rogovchenko, YV (Academic Press Inc Elsevier Science, 2004)
We are concerned with the nonexistence of L-2-solutions of a nonlinear differential equation x = a(t)x + f (t, x). By applying technique similar to that exploited by Hallam [SIAM J. Appl. Math. 19 (1970) 430-439] for the study of asymptotic behavior of solutions of this equation, we establish nonexistence of solutions from the class L-2 (t(0), infinity) under milder conditions on the function a (t) which, as the examples show, can be even square integrable. Therefore, the equation under consideration can be classified as of limit-point type at infinity in the sense of the definition introduced by Graef and Spikes [Nonlinear Anal. 7 (1983) 851-871]. We compare our results to those reported in the literature and show how they can be extended to third order nonlinear differential equations. (C) 2004 Elsevier Inc. All rights reserved.
Keywords: nonlinear differential equations; second order; limit-point/limit-circle classification; square integrable solutions